Capacitação docente: eficaz para as práticas de comunicação não violenta - Coltri, Ana Maria Nastri Manfredini (2021)
Introduction: The violence present in contemporary society has become a relevant issue in the school and community environment, as a need for changes for more positive human relationships. Nonviolent Communication (CNV) seeks to resolve conflicts through various practices that encourage compassion and empathy. Objective: to train teachers of secondary education integrated to technical, to use the principles of the CNV, in order to spread the culture of peace. Methodology: exploratory, descriptive, prospective study with a qualitative approach. The research was approved by the Research Ethics Committee of the Faculty of Medical and Health Sciences of the Pontifical Catholic University of São Paulo. Semi-structured interviews were conducted with 35 teachers and 40 students, seeking to analyze how communication and conflict management take place in the school environment. The professors were then divided into an experimental group (n=20), which participated in two workshops using the CNV tools, and a control group (n=15), which did not receive any intervention. After the workshops, the students, blind about which teachers participated in the workshops, were again interviewed to point out indicators whether or not the awareness of the teachers and the relation to the CNV occurred. Data collection took place virtually using the Teams platform, from March to May 2021. For the interpretation of qualitative data, Laurence Bardin's content analysis method was used. Results: Students and teachers identified changes in the behavior of participants in the experimental group, creating more assertive and less violent communication alternatives in dealing with conflicts within the school. In addition, they began to value and respect more individual and collective experiences, diversities and experiences, expanding their understanding of themselves and their belonging in the school environment. Conclusion: the professors of the experimental group were sensitized and trained to use the pillars that guide the CNV, fostering and being multipliers of a culture of peace